IMF Research Bulletin, September 2014. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2014)
This issue of the IMF Research Bulletin opens with a letter from the new editor, Rabah Arezki. The Research Summaries are a "Primer on 'Global Liquidity'" (Eugenio Cerutti, Stijn Claessens, and Lev Ratnovski); and "Trade Integration adn Business Cycle Synchronization" (Kevin Cheng, Romain Duval, and Dulani Senevirante). The Q and A column looks at "Seven Questions on the Global Housing Markets" (Hites Ahir, Heedon Kang, and Prakash Loungani). September 2014 issue of the Bulletin also includes updates on IMF Working Papers, Staff Discussion Notes, and Recommended Readings from the IMF Bookstore, as well as special announcements on new staff publications and the Fifteenth Annual Jacques Polak Research Conference. Also included is information on the latest issue of 'IMF Economic Review' with a link to an article by Paul Krugman.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet